Solutions of the buoyancy-drag equation with a time-dependent acceleration. (21st December 2017) - Bouquet, Serge E.; Conte, Robert; Kelsch, Vincent; Louvet, Fabien
Abstract : We perform the analytic study of the buoyancy-drag equation with a time-dependent acceleration γ ( t ) by two methods. We first determine its equivalence class under the point transformations of Roger Liouville, and thus for some values of γ ( t ) define a time-dependent Hamiltonian from which the buoyancy-drag equation can be derived. We then determine the Lie point symmetries of the buoyancy-drag equation, which only exist for values of γ ( t ) including the previous ones, plus additional classes of accelerations for which the equation is reducible to an Abel equation. This allows us to exhibit two régimes for the asymptotic (large time t ) solution of the buoyancy-drag equation. It is shown that they describe a mixing zone driven by the Rayleigh–Taylor instability and the Richtmyer–Meshkov instability, respectively.